HOPE hospital provides clinical care for the women affected with fistula in Coxs Bazar, Bangladesh. - Mahmood, Iftikher (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To highlight the fistula care and the psychosocial impact of fistula victims in the refugee population in the midst of a massive humanitarian crisis. Scenario: Since August 2017 massive influx of over 800,000 Rohingya people took place in Cox’s Bazar, Bangladesh TheRohingya women have a very high risk to develop obstetric fistula. Rohingya State is one the poorest states in Myanmar, with ghetto-like camps and a lack of basic services and opportunities. In 1982, a new citizenship law was passed, effectively rendering the Rohingya stateless. As a result of the law, their rights to access health services have been restricted. Now many Rohingya are living in Coxs Bazar in tent-bases refugee camps under extremely poor conditions without access to proper medical care, hygiene, sanitation, food or education.The lack of proper maternal health care, together with; early marriage, malnutrition, poverty and the physical characteristics of the women in this community (small body shapes), exposures this women into a very dangerous position with high chances of developing obstetric fistula during childbirth.Many of the Rohingya women are found to have obstetric fistula. HOPE hospital is recommended as the referral center and only provider of fistula care. Since August, many fistula repair have been carried out on Rohingya women at HOPE Hospital